Natural Variation of Leaf Thickness and Its Association to Yield Traits in indica Rice - Chuan-guang LIU; Xin-qiao ZHOU; Da-gang CHEN; Li-jun LI; Ju-chang LI; You-ding CHEN (Journal of Integrative Agriculture, 2014)
Leaf thickness is an important morphological trait in rice. Its association to the yield potential, as of now has not been documented because of the shortage of the equipment which could conveniently measure the leaf thickness in rice. In this study, the thickness of top three leaves of 208 cultivars had been determined by a nondestructive rice leaf thickness instrument for the research of the natural variation of leaves thickness and its association to yield traits in indica rice. The results showed that the flag leaf was the thickest, and the 2nd leaf was thicker than the 3rd leaf. Analysis of variance indicated the existence of wide genetic diversity of leaf thickness among the investigated indica rice genotypes. The tight correlation among the thicknesses of the top three leaves means that the leaf thickness traits share one genetic control system. Leaf thickness had a significant positive correlation with leaf length and a positive correlation with leaf width, indicated that thicker leaf was beneficial to increasing the single leaf area. The results of correlation analysis revealed that thicker leaf should be profitable to the leaf erection, higher numbers of grains per panicle and higher grains weight per panicle. However, the significantly negative correlation between leaf thickness and number of panicles per plant counteracted the profitability from increased grains weight per panicle, so that the correlations of the thicknesses of the top three leaves to yield and biomass were positive but not significantly. It has made great progress in the genetic improvement of leaves thickness in inbred indica rice breeding in Guangdong Province, China, since the 1990s.